2016
DOI: 10.1111/tmi.12655
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/Rif for the diagnosis of extrapulmonary tuberculosis – an experience from a tertiary care centre in South India

Abstract: Abstractobjective The Xpert MTB/Rif, with a detection limit of 131 CFU/ml, plays a valuable role in the diagnosis of extrapulmonary tuberculosis, both susceptible and resistant. This study aims at evaluating the Xpert MTB/Rif for the same, at a tertiary care centre in south India, assessing it against both culture and a composite gold standard (CGS).methods We tested consecutive samples from patients suspected of extrapulmonary tuberculosis with Xpert MTB/Rif, evaluated its sensitivity and specificity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…We identified 66 unique studies that met the inclusion criteria (Ablanedo‐Terrazas 2014; Al‐Ateah 2012; Arockiaraj 2017; Bahr 2015; Bahr 2017; Bera 2015; Bholla 2016; Biadglegne 2014; Blaich 2014; Causse 2011; Che 2017; Christopher 2013; Coetzee 2014; Dhasmana 2014; Dhooria 2016; Diallo 2016; Du 2015; Feasey 2013; Friedrich 2011; Ghariani 2015; Gu 2015; Gursoy 2016; Hanif 2011; Held 2014; Held 2016; Hillemann 2011; Ioannidis 2011; Iram 2015; Jing 2017; Kim 2015a; Li 2017; Ligthelm 2011; Lusiba 2014; Malbruny 2011; Massi 2017; Mazzola 2016; Meldau 2014; Nataraj 2016; Nhu 2014; Ozkutuk 2014; Pandey 2017; Pandie 2014; Patel 2013; Penata 2016; Pink 2016; Pohl 2016; Rufai 2015; Rufai 2017a; Rufai 2017b; Saeed 2017a; Safianowska 2012; Scott 2014; Sharma 2014; Sharma 2016; Solomons 2016; Suzana 2016; Tadesse 2015; Teo 2011; Tortoli 2012; Trajman 2014; Ullah 2017; Vadwa...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 66 unique studies that met the inclusion criteria (Ablanedo‐Terrazas 2014; Al‐Ateah 2012; Arockiaraj 2017; Bahr 2015; Bahr 2017; Bera 2015; Bholla 2016; Biadglegne 2014; Blaich 2014; Causse 2011; Che 2017; Christopher 2013; Coetzee 2014; Dhasmana 2014; Dhooria 2016; Diallo 2016; Du 2015; Feasey 2013; Friedrich 2011; Ghariani 2015; Gu 2015; Gursoy 2016; Hanif 2011; Held 2014; Held 2016; Hillemann 2011; Ioannidis 2011; Iram 2015; Jing 2017; Kim 2015a; Li 2017; Ligthelm 2011; Lusiba 2014; Malbruny 2011; Massi 2017; Mazzola 2016; Meldau 2014; Nataraj 2016; Nhu 2014; Ozkutuk 2014; Pandey 2017; Pandie 2014; Patel 2013; Penata 2016; Pink 2016; Pohl 2016; Rufai 2015; Rufai 2017a; Rufai 2017b; Saeed 2017a; Safianowska 2012; Scott 2014; Sharma 2014; Sharma 2016; Solomons 2016; Suzana 2016; Tadesse 2015; Teo 2011; Tortoli 2012; Trajman 2014; Ullah 2017; Vadwa...…”
Section: Resultsmentioning
confidence: 99%
“…In the index test domain, we thought that all studies had low risk of bias because Xpert test results are automatically generated, the user is provided with printable test results, and the test threshold is prespecified. Regarding applicability, we thought that 42 studies (64%) had low concern because at least 75% of the specimen types in these studies were processed according to WHO recommendations, and 21 studies (32%) had high concern because less than 50% of the specimen types in these studies were processed according to WHO recommendations (Arockiaraj 2017; Causse 2011; Che 2017; Dhasmana 2014; Feasey 2013; Friedrich 2011; Held 2014; Held 2016; Lusiba 2014; Malbruny 2011; Nhu 2014; Pandey 2017; Pohl 2016; Rufai 2015; Rufai 2017a; Rufai 2017b; Suzana 2016; Teo 2011; Tortoli 2012; Ullah 2017; Zeka 2011). Three studies (5%) had unclear concern because the manner of specimen processing was not reported (Bera 2015; Ioannidis 2011), or only 50% of the specimen types were processed according to WHO recommendations (Christopher 2013).…”
Section: Resultsmentioning
confidence: 99%
“…20 Because of low bacillary load and its detection limit of 131cfu/ml might be the reason for CBNAAT negativity in these patients. 21 According to WHO Xpert guidelines above 23/42 patients they had received Tb treatment as they were cytologically positive and clinically suspicious. 22 So, CBNAAT negative result can still have Tb or MOTT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of pathological diagnosis are closely related to the location of the biopsy site, the quality of equipment, and the experience of the physician. CRS classifies TB based on positive results from one of the several criteria, including culture, clinical manifestation, histopathology, imaging, and response to treatment, resulting in the reclassification of false positives to true positives and increased specificity and PPV [ 28 ].…”
Section: Discussionmentioning
confidence: 99%